(untitled) (Canadian Oncology Today, 2025)
Breast cancer remains the most common cancer among women globally, with significant morbidity and mortality. Current treatment for breast cancer, both in the early stage and metastatic setting, is based on a tumour biopsy and immunohistochemical detection of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor 2 (HER2) expression. Though substantial research has been undertaken over the years to establish new prognostic and predictive biomarkers in breast cancer, most have not demonstrated significant clinical utility. Circulating tumour DNA (ctDNA) is increasingly used across various cancer types for precision medicine. In this article, we discuss the current roles of ctDNA in breast cancer prognosis and its clinical utility in treatment decision-making in early- and advanced-stage settings.